The Basle scuritisation framework explained: The regulatory treatment of asset securitisation - Andreas A. Jobst (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
The paper provides a comprehensive overview of the gradual evolution of the supervisory policy adopted by the Basle Committee for the regulatory treatment of asset securitisation. We carefully highlight the pathology of the new 'securitisation framework' to facilitate a general understanding of what constitutes the current state of computing adequate capital requirements for securitised credit exposures. Although we incorporate a simplified sensitivity analysis of the varying levels of capital charges depending on the security design of asset securitisation transactions, we do not engage in a profound analysis of the benefits and drawbacks implicated in the new securitisation framework.
urn:nbn:de:hebis:30-10725
Keywords: E58; G21; G24; K23; L51; 330; Banking Regulation; Asset Securitisation; Basle Committee; Basle 2